PENENTUAN RUTE PENGAMBILAN SAMPAH DI KOTA MERAUKE DENGAN METODE SAVING HEURISTIC - Perwitasari, Endah Wulan; Subanar, Subanar (Universitas Bina Darma, 2013)
Waste distribution problem has the common characteristics of the poor of scheduling and poor establishing route of waste. The waste distribution problems cover several issues such as the selection the route for the vehicle and the minimizing the distribution cost. The waste collection route is modeled into Vehicle Routing Problem (VRP). VRP is the selection of which route used by the dump trucks. The purpose of VRP is to minimize the time, distance, and distribution cost. There are two methods to deal with the VRP problems, which are the exact and heuristic methods. The exact method aimed to the optimum result, whereas heuristic method put emphasis on near-to-optimum but with quicker computing time. The result obtained by this research is the combination between exact and heuristic method. This combination is successfully implemented and it is able to determine which route to fulfill the problems of waste distribution. Keywords: Waste Collection Route, Algorithm, VRP, and Saving Heustic